[Gábor Radnai 4]
old lady walking with woman & boy, boy listening transistor radio, travelling with Rákóczi ship on the Danube, at some ruins, on the street, trams, footbal, in the Balaton, trabant, in front of the weekend house, old Czech Skoda, Móricz Zsigmond Square, baby, All the family, boy with a ship model,